Size Design Method of Two-phase Ejector - Du Yanjun; Liu Feng; Liu Yunfa; Zhang Bo (Zhileng xuebao)
Based on the basic rules of the flow process, a set of dimensional correction coefficients is introduced according to the design method of the liquid–liquid ejector. The optimum correction coefficient is determined using an experimental verification method, and the design method of the liquid–liquid ejector in the jet refrigeration cycle is proposed. Experiments using R22 as a refrigerant, a two-phase ejector, and a full-liquid ejector replacing the dry evaporator in a traditional compression refrigeration cycle were conducted to achieve a jet refrigeration cycle. Labview8.5 was applied as the real-time data collector. Through a data analysis, it was found that the injection coefficient of the injector is the highest when the correction value is δ = 0.95, and then drops. When the operating conditions of the injector are a working pressure of 0.95 MPa, ejecting pressure of 0.45 MPa, mixing pressure of 0.5 MPa, and correction coefficient of δ = 0.95, the working conditions of each measuring point are in accordance with the design conditions, and the error between the measured value of the injection coefficient and the empirical formula is less than 3%, proving that the design method for this dimension is feasible.